2021
DOI: 10.1002/ett.4337
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain technology for the industrial Internet of Things: A comprehensive survey on security challenges, architectures, applications, and future research directions

Abstract: The blockchain has emerged as an innovative and powerful technology that shows the tremendous potential to enhance the smart industrial frameworks by providing encryption, immutable storage, and decentralization. In the past few years, several applications in the industrial Internet of Things (IIoT) have emerged and blockchain technologies gained great attention from academia and industry. To discover the great potential of blockchain technology for the IIoT, we present a comprehensive survey on security issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 134 publications
(133 reference statements)
1
20
0
Order By: Relevance
“…A study by Latif et al [90] showed that BC can benefit IIoT in many aspects. Another study by Latif et al [91] also focused on BC application in IIoT as an important technology that can enhance security and trust in The main focus of the articles which are reviewed in this study was also based on the new conceptual/theoretical frameworks. For example, Wamba et al [41], Saurabh and Dey [52], Xu et al [66], and Aslam et al [42] developed new frameworks based on the factors/barriers introduced in their studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Latif et al [90] showed that BC can benefit IIoT in many aspects. Another study by Latif et al [91] also focused on BC application in IIoT as an important technology that can enhance security and trust in The main focus of the articles which are reviewed in this study was also based on the new conceptual/theoretical frameworks. For example, Wamba et al [41], Saurabh and Dey [52], Xu et al [66], and Aslam et al [42] developed new frameworks based on the factors/barriers introduced in their studies.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Latif et al [90] showed that BC can benefit IIoT in many aspects. Another study by Latif et al [91] also focused on BC application in IIoT as an important technology that can enhance security and trust in the system. Blockchain application in smart grids in order to improve the security is investigated in different studies as well [92,93].…”
Section: Discussionmentioning
confidence: 99%
“…At present, China's NB-IoT industrial development is also in a leading position in the world. Reference [11] clearly proposed that the infrastructure of narrowband IoT should be built and perfected to achieve its large-scale application in urban ones. In the five-year plan for the development of the information and communications industry (2016-2020), the Ministry of Information and Communications has clearly proposed to build and improve the infrastructure of narrowband IoT and realize its large-scale application in urban management and key industries, and issued a notice on comprehensively promoting the construction and development of mobile IoT [12].…”
Section: Related Workmentioning
confidence: 99%
“…The IIoT framework contains multiple intelligent and connected devices to establish a smart industrial setup [170]. These devices include sensors, actuators, and controllers that use different DL algorithms for the learning process.…”
Section: Lightweight Learning Frameworkmentioning
confidence: 99%